GE_GERICHTE P/19549/2019 vom 10. März 2025 - GE Cour de justice (2025)
RETRAIT(VOIE DE DROIT);LÉSION CORPORELLE SIMPLE;CONTRAINTE(DROIT PÉNAL);VOIES DE FAIT;AGGRAVATION DE LA PEINE;DÉFENSE D'OFFICE | CP.181; CP.123.ch1; CPP.407.al1.leta; CPP.126; CPP.49; CPP.135